The Mediating Role of Purchase Intention on Green Skincare Purchase Behavior - Aisyah Rara Fauzia; Fredianaika Istanti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The skincare sector in Indonesia has experienced swift growth and has become an integral part of consumers' daily routines. This upward trend in usage has brought about concerns for the environment, prompting the introduction of green skincare options as a more sustainable choice. Even with this transition, enthusiasm for green products does not necessarily translate into corresponding purchase action. This study aims to examine the influence of product knowledge and environmental awareness influence purchase intentions and their effects on the purchase behavior regarding local green skincare items, treating purchase intention as a mediating factor. This study uses a quantitative approach through a survey of skincare users in Semarang City as the research population, with purposive sampling techniques applied to 180 respondents who meet the criteria of skincare consumers. The data is analyzed using SEM-PLS method. The findings indicate that both product knowledge and environmental concern significantly influence purchase intention, while purchase intention and environmental concern play a significant role in influencing purchase behavior. However, there is no direct influence of product knowledge on purchasing actions. Additionally, purchase intention serves as a mediator in the connections between product knowledge and purchase behavior, as well as between environmental concern and purchase behavior.